2004
DOI: 10.1002/rcm.1560
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N2O on the isotopic composition of air‐CO2 samples

Abstract: The ionisation efficiencies of N2O vs. CO2 as well as their ratios were measured in detail introducing clean N2O and CO2 into the electron impact ion source of an isotope ratio mass spectrometer. Changes in the ionisation efficiency ratio (IER) were found for different electron energy settings and compared with the ratios of literature ionisation cross-section values for pure N2O and CO2. To establish the influence of mixtures of N2O and CO2 in a mass spectrometer, artificial air mixtures were prepared by mixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 9 publications
3
25
1
Order By: Relevance
“…The value of E N2O determined on our MAT 252 mass spectrometer on pure N 2 O compared with CO 2 (filled in the same bellow to the same pressure) was slightly variable around 0.71 over a period of several years. It has been reported that E N2O determined on pure gases can deviate from the effective value characterizing the N 2 O behaviour in CO 2 þN 2 O air mixtures, [29][30][31] but for our MAT 252 the deviation appeared to be not significant, as shown below. In a dedicated study, 31 31 ).…”
contrasting
confidence: 46%
“…The value of E N2O determined on our MAT 252 mass spectrometer on pure N 2 O compared with CO 2 (filled in the same bellow to the same pressure) was slightly variable around 0.71 over a period of several years. It has been reported that E N2O determined on pure gases can deviate from the effective value characterizing the N 2 O behaviour in CO 2 þN 2 O air mixtures, [29][30][31] but for our MAT 252 the deviation appeared to be not significant, as shown below. In a dedicated study, 31 31 ).…”
contrasting
confidence: 46%
“…5). Factors contributing to the uncertainty are the correction for N 2 O present in the analyzed gas (the correction for the m/z 46 ion current is larger than that for m/z 45; see Sirignano et al, 2004;Ghosh and Brand, 2004), the δ 18 O value used for digesting the calcite during standardization (Wendeberg et al, 2011) and the 17 O correction . The latter have been the focus of the WMO recommendations for several years, where the need for a unified use of the Assonov correction has been emphasized (Assonov et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Further inconsistencies were found in the correction procedures for the 17 O contribution used when translating ion currents into delta values and in the algorithms applied for removing the inevitable presence of N 2 O in the CO 2 gas extracted from air cryogenically (Sirignano et al, 2004;Ghosh and Brand, 2004). …”
Section: State Of Affairsmentioning
confidence: 99%
“…The ensuing discussion assumes that the measured 45 d and 46 d values have been, if necessary, corrected for cross-contamination between sample and working reference gas Rama Rao and Bindal, 2001) and, in the case of atmospheric CO 2 samples, for isobaric N 2 O interference at m/z 44, 45 and 46 Craig and Keeling, 1963;Mook and van der Hoek, 1983;Mook and Jongsma, 1987;Ghosh and Brand, 2004;Sirignano et al, 2004;Assonov and Brenninkmeijer, 2006).…”
Section: Definition Of D Valuesmentioning
confidence: 99%